Semantic Web and Linked (Open) Data - Gardašević, Stanislava (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
One of the recent topics in librarianship is the application of Semantic Web and Linked (Open) Data technologies for the purpose of library metadata management. The first part of this paper gives an overview of the basic principles and models of the Semantic Web (XML, RDF, URI, ontologies etc.), as well as the current usage of these principles in libraries and other cultural institutions, with main accent on the usage within Europeana, so called European digital library, archive and museum. The second part of the paper looks at Linked (Open) Data as a constituent and indispensable part of the Semantic Web. In addition to the main principles, it states the key advantages of publication of library matadata as Linked (Open) Data for the institutions as well as for the users. Also, some of the initiatives that have made such efforts are listed. Finally, the recommendation is given for reconsidering library practice in purpose of service improvements and better visibility of library data.